The extraordinary legal policy for Corruption Crimes in shifting the formulation of attempted crimes as perfect crimes. - Nina Zainab (Siber Nusantara Review & Yayasan Sinergi Inovasi Bersama (SIBER), 2024)
The regulation of criminal acts of attempt is known in the Criminal Code, especially in article 53, which states